Pembelajaran Berbasis Online Aplikasi Quizizz Untuk Meningkatkan Pemahaman Mahasiswa Pada Mata Kuliah Pengembangan Profesi Guru Di UIN Raden Fatah Palembang - Wiga Ananda; Wasith Achadi; Fitri Oviyanti; Muhammad Al Ghazali (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
All educational institutions ought to create an effective learning for supporting student understanding. One of application to improve student understanding is Quizizz. This study aims to analyze the implementation of online-based learning by Quizizz to improve collegian understanding. A qualitative research with an analytical descriptive method. Data was collected by interviews and documentation. Steps analyze data using the Miles and Huberman model of the researcher as a human instrument, data reduction, presentation and conclusion. The research subject are collegian of FITK Islamic Stated University Raden Fatah Palembang. The result of this research are : Quizizz application make lectures active and fun because all of collegian involved the game. By Quizizz, collegian can understand the course more easily. The collegian Understanding can seen in answering question successly before 82,48 and after 83,18 which improved 0,84%. The problem are due to network connection and some collegian are not familiar with Quizizz application.